Autonomia e responsabilità nella amministrazione delle risorse della Chiesa - MIÑAMBRES, JESÚS (Prawo Kanoniczne, 2017)
To determine the responsibility for juridical acts, one must first establish the limits of the agent's autonomy. This article studies the limitations of the autonomy of juridical persons, administrators, and other faithful in the management of the resources entrusted to the Church's institutions.